FORMULATION AND EVALUATION OF FAST DISSOLVING ORAL FILMS OF TERBUTALINE SULPHATE USING 32 FULL FACTORIAL DESIGN - Meel, Rakesh Kumar; Chauhan, Dr. C. S. (Asian Journal of Pharmaceutical Research and Development, 2016)
Fast dissolving films are playing an important role in the current pharmaceutical drug delivery systems. They have convenience and ease of use over solid and liquid dosage forms. In the present research, fast dissolving oral film of terbutaline sulphate were developed for treatment of asthma in pediatric and geriatrics using HPMC K15 LV as film forming polymer, SSG as superdisintegrant and PEG-400 as plasticizer. The films were prepared by solvent casting method. Optimization of HPMC E15 LV, SSG and PEG-400 was carried out using 32 full factorial designs. The formulated films of terbutaline sulphate were evaluated for their physic-mechanical parameters like disintegration time, tensile strength, percent elongation, folding endurance and In-vitro drug release. Estimation of drug content uniformity of terbutaline sulphate films was performed and the results were satisfactory. Optimized batch F3 has thickness (0.188±0.001mm), disintegration time (13.40±1.81 sec.) tensile strength (1.35±0.183 Mpa), % Elongation (30.27±1.81), folding endurance (152±6.83), CPR1min 66.214±1.27and CPR10min 98.978±2.49.